(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Background: Despite adherence has been researched in many fields of medicine, there aren’t many studies that specifically address it in relation to dermatology. Objectives: This review’s objective is to provide an overview of the most recent research on dermatology-specific medical adherence. Methods and Materials: Between the years 1985 and 2005, we searched PUBMED using the phrases [adherence AND dermatology] and [dermatology AND therapy]. The search was restricted to human subjects and English-language articles. Results: 57 papers were found in the literature search. In order to define, measure, quantify, validate, and comprehend adherence in dermatology, seventeen of these papers were examined. Conclusions: Because topical therapy adherence among dermatological patients is difficult to gauge accurately, there aren’t many papers on the subject. New electronic monitoring equipment has been used in a small number of studies that have revealed low treatment regimen adherence rates among dermatology patients. Patient non-adherence is influenced by socioeconomic, cognitive, and psychological aspects. Patient adherence can be increased through increasing patient education and the doctor-patient relationship.